Correlative Localization Analysis Between mRNA and Enhanced Green Fluorescence Protein-Fused Protein by a Single-Molecule Fluorescence in situ Hybridization Using an egfp Probe in Aspergillus oryzae - Morita, Yuki; Katakura, Yoshinori; Takegawa, Kaoru; Higuchi, Yujiro (Frontiers in Fungal Biology, 2021)
Although subcellular localization analysis of proteins fused with enhanced green fluorescence protein (EGFP) has been widely conducted in filamentous fungi, little is known about the localization of mRNAs encoding the EGFP-fused proteins. Here, we performed single-molecule fluorescence in situ hybridization (smFISH) using an egfp probe to simultaneously visualize EGFP-fused proteins and their mRNAs in the filamentous fungus Aspergillus oryzae hyphal cells. We investigated the subcellular localization of mRNAs encoding cytoplasmic EGFP, an actin marker protein Lifeact tagged with EGFP and several EGFP-fused proteins AoSec22, AoSnc1, AoVam3 and AoUapC that localize to endoplasmic reticulum (ER), the apical vesicle cluster Spitzenkörper, vacuolar membrane and plasma membrane, respectively. Visualization of these mRNAs by smFISH demonstrated that each mRNA exhibited distinct localization patterns likely depending on the mRNA sequence. In particular, we revealed that mRNAs encoding the vacuolar membrane protein AoVam3 and the plasma membrane purine transporter AoUapC were predominantly localized at the apical cell, suggesting certain mechanism to regulate the existence of these transcripts among hyphal regions. Our findings provide the distinct localization information of each mRNA in A. oryzae hyphal cells.